Korelasi Produksi Bawang Merah (Allium ascolocium L.) Kabupaten Kediri dan Penggunaan Beragam Jenis Pupuk - Wahyudi Wally; Tutut Dwi Sutiknjo; Widi Artini; Nina Lisanty (Universitas Kadiri, 2022)
Fertilizer plays an important role in plant growth and yield. Shallot (Allium ascolocium L.) in its production process utilizes various types of fertilizers to achieve optimal production goals. In recent years, shallot has become a favorite commodity for farmers in Kediri Regency to cultivate because of its promising agribusiness prospects. The main problem for farmers is the diverse use of fertilizers depending on the availability and experience of farming alone. Based on these considerations, the study was conducted on a group of shallot farmers in Kediri Regency to analyze the effect of fertilizer type on production. Multiple regression analysis was employed in this study with independent variables, namely Za, Urea, Manure, KCl, Nitrophoska, Mutiara, Patent-Kali, and Fertiphos fertilizer, while the dependent variable was shallot production. The results showed a significant effect between the utilization of various fertilizers on the production of shallot. However, the use of most types of fertilizers for production, individually, did not affect the production of shallot. Only KCl and Mutiara fertilizer significantly affected the production of shallot. The addition of the use of KCl and Mutiara fertilizer had an impact on changes in the amount of shallot production.